알레르기성 鼻炎의 침구치료에 관한 문헌적 고찰 - 최원구(Won-Goo Choi); 염승철(Seung-Chul Yeom); 이건목(Geon-mok Lee) (동의생리병리학회지, 2006)
The purpose of this study is to investigate the acupuncture points and the The Meridians and Collaterals which are often applicable to Allergic Rhinitis treatment and to help us do a clinical diagnosis. In my discretion, to study Allergic Rhinitis, investigating rhinitis, syuffy nose and nasal mucus is essential. And I investigated the acupuncture points and The Meridians and Collaterals and dialectic patterns which are useful for the acupuncture and moxibustion treatment. I also investigated the correlation of the acupuncture points, and The Meridians and Collaterals and other dialectic patterns. The order of frequency in use of The Meridians and Collaterals is The Governer Vessel, The Large Intestine Meridian of Hand-Yangming, The Bladder Meridian of Foot-Taiyang and the order of frequency in moxibustion is The Governer Vessel, The Large Intestine Meridian of Hand-Yangming. In the acupuncturation of stuffy nose, there are 33 points, and the order of frequency in use is LU20, GV23, LU4, GB15, GV20, BL7, GV22. In the acupuncturation of nasal mucus, there are 21 points, and the order of frequency in use is LU20,, GV23, GV16, GV26, BL12, GV20, GB20. It is thought that acupuncture points LU20, GV23, LU4 can go through the nasal cavity and remove wind fever. And those are used for the face and the five sensory organs diseases. It means that those acupuncture points have similar efficacy. It is thought that The Meridians and Collaterals of The Governer Vessel, The Large Intestine Meridian of Hand-Yangming, The Bladder Meridian of Foot-Taiyang go on a patrol near nose and cure nose disease. KCI Citation Count: 0